Discordant Post-natal Patterns in Fetuses With Heterotaxy Syndrome: A Retrospective Single-Centre Series on Outcome After Fetal Diagnosis - Seidl-Mlczoch, Elisabeth; Kasprian, Gregor; Kitzmueller, Erwin; Zimpfer, Daniel; Steiner, Irene; Jowett, Victoria; Stuempflen, Marlene; Wielandner, Alice; Ulm, Barbara; Michel-Behnke, Ina (Frontiers in Pediatrics, 2022)
Objectives The aim of the study was to evaluate cardiac and extracardiac anomalies in 46 prenatally detected cases of heterotaxy, to describe the postnatal outcome and to analyse discordant postnatal patterns of isomerism classified in the fetus. Methods Fetuses with the diagnosis of heterotaxy from 1998-2019 in a tertiary referral center were retrospectively analysed. Prenatal and postnatal diagnoses of cardiac and extracardiac malformations were systematically reviewed. Surgical interventions and long term outcome were assessed for surviving infants. The subgroup definition of isomerism was reviewed postnatally with further imaging studies. Results Forty-six fetuses with heterotaxy and cardiovascular pathology, of which 28 (61%) had LAI and 18 (39%) RAI, were included. Parents chose termination of pregnancy in 12/46 (26%). 25% (7/28) fetuses with LAI had AV Block, with 4 cases of hydrops (14%). Extracardiac anomalies were present in 35%. There were 63% (29/46) live births. (LAI 62%, RAI 65%), five fetuses were lost to follow up. At the time of 1 year, 67% [48%; 92%] of the patients with LAI were alive and 55% [32%; 94%] of the patients with RAI. At the time of 5 years the estimates were 67% [48%; 92%] in the LAI group and 46% [24%; 87%] in the RAI group. Median survival (Q1; Q3) was 11. 1 (0.1; 14) years for patients with LAI and 1.3 (0.09; NA) years for patients with RAI. Of 17 children who had undergone cardiac surgery, five (29%) achieved a biventricular repair and 11 (65%) a univentricular palliation. Three were primarily palliated but converted to biventricular thereafter. Fetal subtype definition of isomerism based on the abdominal situs and postnatal thoracic imaging studies showed a discordant pattern of bronchopulmonary branching and atrial appendage anatomy in 40% of our live born children. Conclusion Heterotaxy is a a rare condition often associated with complex cardiac disease and extracardiac anomalies than can be diagnosed prenatally. Due to the complexity of this entity termination rates are high and long-term outcome can be difficult to predict due to the wide spectrum of cardiac and extracardiac abnormalities and small numbers of patients in published series.